Nursing prescription and quality of care: a documental study - Larissa Gutierrez da Silva; Denise Albieri Jodas; Simone Cristina Baggio; Dagmar Willamowius Vituri; Laura Misue Matsuda (Universidade Federal de Santa Maria, 2012)
Objective: to analyze the quality indicator Nursing Prescription of a Public University Hospital of North of Parana. Metod: a retrospective documentary. We analyzed 11,663 Nursing Prescriptions from units of hospital medical-surgical, for the period 2001 to 2008. Results: when compared to standard 80%, items relating to the "realization of the prescription by the same nurse who admitted the patient," "indication of pre operative/exams care" and "indication of postoperative/exams care" were those with the lowest percentage of completion "Correct"(respectively 60.8% and 62.4%, 57.1%). The item "presence of a daily prescription for each patient" had the best result in terms of the completeness "Correct" (88.5%). Considerations: in the institution investigated the practice of Nursing Prescription needs to be revisited and improved, because if found that the 10 items assessed, only three reached the set standard